2013
DOI: 10.1088/1748-9326/8/4/045025
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying landscape change in an arctic coastal lowland using repeat airborne LiDAR

Abstract: Increases in air, permafrost, and sea surface temperature, loss of sea ice, the potential for increased wave energy, and higher river discharge may all be interacting to escalate erosion of arctic coastal lowland landscapes. Here we use airborne light detection and ranging (LiDAR) data acquired in 2006 and 2010 to detect landscape change in a 100 km 2 study area on the Beaufort Sea coastal plain of northern Alaska. We detected statistically significant change (99% confidence interval), defined as contiguous ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 37 publications
0
49
0
Order By: Relevance
“…White and Wang (2003) and Young and Ashford (2006) used repeat airborne LiDAR data to estimate volumetric erosion and sediment pathways of non-permafrost coasts. Jones et al (2013) demonstrated suitability of airborne LIDAR data for landscape changes of arctic coastal lowlands, including volumetric changes due to coastal erosion.…”
Section: Introductionmentioning
confidence: 94%
“…White and Wang (2003) and Young and Ashford (2006) used repeat airborne LiDAR data to estimate volumetric erosion and sediment pathways of non-permafrost coasts. Jones et al (2013) demonstrated suitability of airborne LIDAR data for landscape changes of arctic coastal lowlands, including volumetric changes due to coastal erosion.…”
Section: Introductionmentioning
confidence: 94%
“…Elevation change accuracy was estimated using the approach of Jones et al (2013). Vertical accuracies of the Ikonos-derived and LiDAR DEM data sets were used to calculate the threshold of considered elevation changes:…”
Section: Accuracy Assessmentmentioning
confidence: 99%
“…This shortcoming is mostly due to the absence of highresolution DEMs for remote polar regions. Recent volumetric erosion studies used stereo-photogrammetrically or LiDAR-derived DEMs (Jones et al 2013;Gü nther et al 2015). Coastal carbon flux calculations were based mainly on the combination of planimetric coastline movement rates and average cliff heights (e.g., Jorgenson & Brown 2005;Ping et al 2011;Gü nther et al 2013) and assumed that coastline retreat correlates with sediment release.…”
Section: Introductionmentioning
confidence: 99%
“…More generally, vertical changes are an excellent proxy for the degradation of ice-rich permafrost soils because thawing causes the soils to lose cohesion and reduce in volume, inducing slumping 5 and subsidence (Günther et al, 2015;Jones et al, 2013). Our estimates of topographic changes are obtained from repeated topographic observations using the radar remote sensing technique single-pass interferometry (Bamler and Hartl, 1998).…”
mentioning
confidence: 99%
“…The ability to cover large areas and to do so frequently are key advantages over both in-situ measurements and the remote sensing techniques photogrammetry and LiDAR (Günther et al, 2015;Jones et al, 2013;Obu et al, 2016). A further advantage is that reliable height measurements can also be made when the soil moisture changes and when the surface structure is disrupted -a common occurrence in rapid mass movements.…”
mentioning
confidence: 99%